2019
DOI: 10.3390/catal9020183
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Fabrication of Supported Ni/SiO2 Catalysts for Dry Reforming of Methane with Remarkably Enhanced Catalytic Performance

Abstract: Ni catalysts supported on SiO2 are prepared via a facile combustion method. Both glycine fuel and ammonium nitrate combustion improver facilitate the formation of much smaller Ni nanoparticles, which give excellent activity and stability, as well as a syngas with a molar ratio of H2/CO of about 1:1 due to the minimal side reaction toward revserse water gas shift (RWGS) in CH4 dry reforming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…As shown in Figure 5b, the H2/CO ratio is lower than one for both catalysts. This result is mainly due to the RWGS reaction and to a less degree to other side reactions [31], such as the reverse Boudouard reaction (C + CO2  2 CO) [49]. The CO and H2 yields are shown in Figure 5c,d, respectively.…”
Section: Catalytic Performance Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure 5b, the H2/CO ratio is lower than one for both catalysts. This result is mainly due to the RWGS reaction and to a less degree to other side reactions [31], such as the reverse Boudouard reaction (C + CO2  2 CO) [49]. The CO and H2 yields are shown in Figure 5c,d, respectively.…”
Section: Catalytic Performance Studiesmentioning
confidence: 90%
“…The Ni@La 2 O 3 /SiO 2 catalyst displays a broad reduction peak at 615 • C, suggesting that Ni-based species have a strong interaction with the support [42,49]. Li et al [42] found that the small NiO particle confined into mesoporous La 2 O 3 strongly interacts with La 2 O 3 support, resulting in a high reduction temperature for NiO.…”
Section: Characterization Of Fresh and Reduced Catalystsmentioning
confidence: 99%
“…The sintering of nickel particles leads to the formation of particle aggregates, decreased activity, and enhanced carbon deposition. It was found that carbon deposits possess a greater tendency to deposit on Ni particles of a larger size [1,6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Modern civilization is confronted with two major challenges: dwindling energy resources [1,2] and global warming caused by greenhouse gases (mainly CH 4 and CO 2 ) [3,4]. The dry reforming of the methane (DRM) reaction for the conversion of greenhouse gases into a valuable synthesis gas (H 2 and CO) product is a potential contestant for confronting both these challenges simultaneously.…”
Section: Introductionmentioning
confidence: 99%